Isoflavone characters of three soybean varieties under drought stress with application of nitrogen sources - Yaya Hasanah; Tengku Chairun Nisa; . Hapsoh; Hamidah Hanum (Syiah Kuala University, 2013)
Human interest in soybean greatly increased in recent years due to the positive effects of secondary metabolites in soybean such as isoflavones for human health. Isoflavones are phytoestrogens worked as the antioxidant and chemopreventive agents for estrogenic compounds that can inhibit cellproliferation. Isoflavones also serves to prevent heart damage, osteoporosis and menopause syndrome, prevent prostate cancer, colon cancer and breast cancer. Daidzein, genistein and glycitein are the major isoflavones in soybean. A research about isoflavone charácters of three soybean varieties under droughtstress with application of Nitrogen sources was conducted in green house, Faculty of Agriculture, University of Sumatera Utara. The aim of the research was to study the effect of Nitrogen sources under drought stress on isoflavone characters of three soybean varieties. The experiment used a Factorial andomized Block Design with three factors and three replications. The first factor was soybean varieties consisted of Anjasmoro, Wilis and Sinabung. The second factor was Nitrogen sources consisted of without N fertilizer application; Urea 50 kg/ha, Bradyrhizobium sp., cow manure 10 t/ha, rice straw compost 10 t/ha. The third factor was soil water content condition namely 50%, 60%, 70 and 80% of field capacity. The parameters observed were isoflavone charcters consisted of genistein, daidzein, glycitein and isoflavone total. The resultshowed that Anjasmoro variety had the genistein, daidzein, glycitein and isoflavone total contents of soybean higher than Wilis and Sinabung. The application of Nitrogen sources increased the genistein, daidzein, glycitein and isoflavone total contents of soybean compared without application of Nitrogensources. There is a distinct pattern in the increase in the isoflavone total content in Anjasmoro, Wilis and Sinabung with increasing the drought stress. At Anjasmoro variety, increasing drought stress caused the elower of isoflavone total content, while the varieties Sinabung and Wilis are the opposite pattern